Overdiagnosis of Asthma in the Community - Jorin Lindensmith; Debra Morrison; Carole Deveau; Paul Hernandez (Canadian Respiratory Journal)
BACKGROUND: Overdiagnosis of asthma may be an emerging problem after years of attention to the rising prevalence and reported underdiagnosis of the disease.